Dual-conductive N, S co-doped carbon nanoflowers for high-loading quasi-solid-state supercapacitor. (18th May 2020) - Chen, Ling; Lian, Cheng; Jiang, Hao; Chen, Lingxue; Yan, Jian; Liu, Honglai; Li, Chunzhong
Highlights: The N, S co-doped carbon possesses high ions and electrons dual conductivity. The DFT calculations reveal that S doping can contribute quantum capacitance. The quasi-solid-state supercapacitors show excellent electrochemical performance. Abstract: To cope the challenges including the low areal energy density and interface engineering between electrode and electrolyte of quasi-solid-state supercapacitors. We herein demonstrate the rational design and synthesis of ion/electron dual-conductive carbon nanoflowers assembled by N, S co-doped two-dimension mesoporous nanosheets. Electronic density functional theory calculations suggest that the S doping could lead to an extra quantum capacitance and suppress the side reactions. The structure characterization suggests that the bigger S atoms could enlarge interlayer distance of carbon from 0.347 nm to 0.378 nm, accelerating ions diffusion kinetics. Consequently, the N, S-C nanoflowers deliver excellent electrochemical performances even the loading mass of N, S-C reaches 6.38 mg cm −2 owing to the good electrical conductivity and low charge transfer resistance. Furthermore, the a symmetrical quasi-solid-state supercapacitor is assembled and delivers a high specific capacitance of 52.5 F g −1 even at 13.5 mg cm −2 and a capacitance retention of 97.2% after 10, 000 cycles.